Complete atrioventricular block on isolated guinea pig heart induced by an aqueous fraction obtained from Psidium guajava L. leaf - Gondim,Antonio N.S. (2006)
This paper aimed to study the electrocardiographic effect produced by the aqueous fraction (AqF) obtained from the acetic extract of Psidium guajava L. leaf on the isolated guinea pig heart. Electrocardiographic records (ECG) were obtained on isolated hearts beating spontaneously or under regular electrical stimulation. The hearts were mounted in a constant flow Langendorff perfusion system. Until 20 mg/mL, AqF did not change the spontaneous cardiac rate (control: 180 ± 9 bpm, test: 182 ± 10 bpm; N = 3; p > 0.05). Concentrations equal or greater then 20 mg/mL induced complete atrioventricular block (AVB). However, this effect promptly disappeared when AqF was removed from the perfusion fluid (N = 3 hearts). The AVB induced by AqF involves heart muscarinic receptors because atropine sulfate (1.5 mM) could prevent the appearance of such disturbance.